Opportunistic adaptations to man-induced habitat changes by some South American Caprimulgidae - Ingels, J.; Oniki, Y. [UNESP]; Willis, E. O. [UNESP] (Instituto Internacional de Ecologia, 1999)
We describe the opportunistic adaptation to man-induced changes in the habitats of six neotropical Caprimulgidae. Habitats created by those changes, and similar to their original and usual ones, are readily occupied by these nightjars. The occasional invasion of urban environments (urbanization) is the most recent and most remarkable behavioural adaptation.

Descrevemos a adaptação oportunista de seis caprimulgídeos neotropicais aos hábitats induzidos pelo homem. Os ambientes criados por essas mudanças e semelhantes aos orginais são prontamente ocupados por esses caprimulgídeos. A invasão de ambientes urbanos (urbanizados) é a mais recente e mais extraordinária adaptação comportamental.
Adaptações às mudanças de hábitat pelo homem em alguns Caprimulgidae da América do Sul
Keywords: habitats; urbanization; neotropical; Caprimulgidae; ambientes; urbanização; neotropical; Caprimulgidae